Desarrollo de un software educativo como recurso didáctico para la asignatura de ciencias naturales del noveno año de educación general básica del colegio de bachillerato “Saraguro”, periodo 2014 – 2015, del cantón Saraguro de la provincia de Loja - Armijos Minga, Carlos Alberto (2015)
The theme developed in this paper is: "EDUCATIONAL SOFTWARE DEVELOPMENT AS A RESOURCE FOR TEACHING THE COURSE OF NATURAL SCIENCES THE NINTH YEAR OF BASIC GENERAL EDUCATION SCHOOL OF BACHELOR" SARAGURO "period 2014 - 2015, SARAGURO CANTON PROVINCE LOJA. ". It has set as its main objective in this research to design and develop a new teaching tool to be applied in the teaching and learning of the subject of Natural Sciences of the ninth year of basic education, using multimedia elements such as videos, animations and activities that facilitate the assimilation of knowledge and encourage independent learning. To run the investigative process, analytical and deductive methods in understanding the nature of the problem and the establishment of relevant solutions are applied. The statistical method for analyzing the data, and the statistical method for making the results and report theses are also used. Regarding the development of educational software it was given by the phases of the cascade methodology including: analysis, design, coding, testing and implementation. The techniques supported this process were the interview and survey which data and information relevant features are extracted educational software. The results showed that the school is able to implement educational software in their educational processes. In the case of Natural Sciences for nine years GBS identifies the types of content such as animations and activities that strengthen and facilitate the understanding of the issues of greatest degree of difficulty found in blocks 4.5 and 6 are needed. The developed educational software is socialized and implemented in the educational institution, leaving it suitable for use in the process of teaching and learning.